1985
DOI: 10.1128/jvi.53.1.81-88.1985
|View full text |Cite
|
Sign up to set email alerts
|

Use of a bacterial expression vector to map the varicella-zoster virus major glycoprotein gene, gC

Abstract: The genome of varicella-zoster virus (VZV) encodes at least three major glycoprotein genes. Among viral gene products, the gC gene products are the most abundant glycoproteins and induce a substantial humoral immune response (Keller et al., J. Virol. 52:293-297, 1984). We utilized two independent approaches to map the gC gene. Small fragments of randomly digested VZV DNA were inserted into a bacterial expression vector. Bacterial colonies transformed by this vector library were screened serologically for antig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

1986
1986
2009
2009

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…Finally, no homology between EHV-1 and EHV-3 U. sequences could be detected under the stringent hybridization conditions used in these studies. Why this region alone should be less conserved than other genomic areas is uncertain, but studies on pseudorabies virus (17,27) and varicellazoster virus (10), which are herpesviruses with a two-isomer type of structure similar to that of EHV-1 and EHV-3, have indicated that coding sequences for important viral glycoproteins are localized within the U, regions of these two viruses. Perhaps the EHV-1 and EHV-3 Us regions encode protein products (such as surface glycoproteins) which im- part some of the differential properties, such as serological type specificity, which serve to distinguish these two viruses.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, no homology between EHV-1 and EHV-3 U. sequences could be detected under the stringent hybridization conditions used in these studies. Why this region alone should be less conserved than other genomic areas is uncertain, but studies on pseudorabies virus (17,27) and varicellazoster virus (10), which are herpesviruses with a two-isomer type of structure similar to that of EHV-1 and EHV-3, have indicated that coding sequences for important viral glycoproteins are localized within the U, regions of these two viruses. Perhaps the EHV-1 and EHV-3 Us regions encode protein products (such as surface glycoproteins) which im- part some of the differential properties, such as serological type specificity, which serve to distinguish these two viruses.…”
Section: Discussionmentioning
confidence: 99%
“…The VZV glycoprotein gI (previously designated gpIV) and gE are encoded by VZV genes 67 and 68, respectively, which are located within the SalI-I DNA fragment ( Fig. 1) of the unique short sequences (Us) of the VZV genome [14,28,29].…”
Section: Vzv Ge (Gpi)mentioning
confidence: 99%
“…The same region of gI is homologous to a region of the VZV protein designated 70K in the original sequencing report (9). In the new nomenclature system this protein is designated gpl (10) and is identified as one of the VZV glycoproteins that has been characterized by monoclonal antibodies (32) and expression in E. coli (13). By insertion of minor gaps in the alignment, six cysteine residues can be aligned, indicating the conservation of what are likely some important disulfide bonds for the structures of these glycoproteins.…”
Section: Gcgatccggagaaaccggaagtgacgaatgggcccaactatggcgtgaccgccagccgccmentioning
confidence: 99%